Development of professional thinking of a teacher in the process of advanced training (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
By professional pedagogical thinking we understand an integral, multi-level reflection and transformation in a generalized form of the objective characteristics of the pedagogical process, determined by its goals and objectives, and the personal characteristics of its participants. The term “professional thinking” began to enter practical and scientific use relatively recently in connection with the significant intellectualization of all social work caused by the scientific and technological revolution.